Visualising SARS-CoV-2 transmission routes and mitigations. (1st December 2021) - Rutter, Harry; Parker, Simon; Stahl-Timmins, Will; Noakes, Catherine; Smyth, Alexandra; Macbeth, Ron; Fitzgerald, Shaun; Freeman, Alexandra L J
Abstract : Harry Rutter and colleagues reflect on the challenges of conveying uncertain estimates for viral transmission in a complex system